International Experience with Private Sector Participation in Power Grids : Brazil Case Study - World Bank Group (World Bank, Washington, DC, 2016)
The power sector which consisted almost exclusively of enterprises under Federal and State control was severely affected by the repercussions of this negative phase for the Brazilian economy. The tariffs for sales between generators and distributors (wholesale trading) and from the latter to end‐consumers (retail sales) were all established by the Brazilian Government. Frequently used as tools for curbing inflation, they fell well below the real costs of the services rendered. As demonstrated below, these tariff constraints had severe consequences for the power generation, transmission and distribution segments in Brazil. A clear awareness of these problems is apparent in the preparation and promulgation of Brazil’s 1988 Constitution, which established that only the Federal Government would be in charge of services and activities linked to power services in Brazil, handled either directly, or through concessions. Tenders will be required to select the concessionaires, either public or private. This was the situation of the Brazilian power sector during the 1990s, fraught with difficulties and with its intra‐sector payment flows severely undermined by the financial situation of the concessionaires, almost all under State control. Quite naturally, many new power generations, transmission and distribution projects ground to a halt, or never even got off the ground, with collateral effects on the construction and equipment industries working with this sector.